Bioefficacy of the Copaiba Oil (Copaifera sp.) in Diets of Laying Hens in the Second Production Cycle in Humid Tropical Climate - Anna Carolina de Souza Hanna,; Cruz , Frank George Guimaraes; Rufino, Joao Paulo Ferreira; Tanaka, Ewerton de Souza; Chagas, Ewerton Oliveira das; Melo, Jadilson Barroncas dos Santos (International Journal of Poultry Science, 2013)
The objective of this study was to evaluate the effect of supplementation of crescent levels (0, 0.10, 0.15, 0.20, 0.25 and 0.30%) of copaiba oil diets on performance, egg quality, biometrics intestines and resistance of the tibia of laying hens in the second production cycle. The experiment lasted 84 days with four intervals of 21 days each. Were used 144 layers Hissex White to 88 weeks of age and were housed in cages 24 used. The experimental design was completely randomized with six treatments and four replications of six birds each. Estimates of the levels of copaiba oil were determined by polynomial regression. The variables feed intake, egg production, feed conversion per dozen eggs, feed conversion per egg mass and egg mass were not significantly influenced (p>0.05) by treatments. The specific gravity of the egg and the percentage of egg shell showed a quadratic effect, getting his best result at the level of 0.15% inclusion of copaiba. The weight of the cecum showed a quadratic effect with his best result in the inclusion of 0.25%. Copaiba oil can be used as an additive in at 0.30% of diets of laying hens. As increased by the inclusion of the oil feed improved the percentage of shell and specific gravity, which may indicate possible relationship of copaiba oil with calcium metabolism.